On the tip of the brain - Paruchuri, Srikanth; Pollock, Timothy G.; Kumar, Naveen (Strategic Management Journal, 2019)
[Research Summary:This study contributes to the reputation spillover literature by showing how a crisis caused by a firm's capability failure enhances the reputations of its rivals. We consider how the combination of rivals' characteristics that increase their associability with the focal firm and the extent to which the crisis is salient in the minds of stakeholders can lead to positive reputation spillovers, and we also explore how long the positive reputation spillover lasts. Using a natural experiment based on the Escherichia coli outbreak in Chipotle's Seattle restaurants, we find that the reputations of other restaurants in the Seattle region were enhanced when the E. coli breakout was more salient and thus cognitively available, but only for Mexican restaurants that were geographically proximal to a Chipotle. Managerial Summary:In this study we conducted a natural experiment based on Chipotle's 2015 E. coli breakout to explore how a firm's capability failure affects the reputation of its competitors. We found that failures due to firm practices that differentiate the firm from others in its industry result in positive reputation spillovers, but only for the firms that are the most similar, and only for as long as the failure is salient to stakeholders. Thus, the benefit to firms from a competitor's failure is only temporary, and will not be experienced equally.]